Workshop on implementing the Agricultural Policy Support Facility (APSF) - Rhoe, Valerie (International Food Policy Research Institute, 2009)
The Agricultural Policy Support Facility (APSF) is an initiative to strengthen pro-poor, gender-sensitive, and environmentally sustainable evidence-based policymaking in Nigeria in the areas of rural and agricultural development. The program is facilitated by the Nigeria Strategy Support Program of the International Food Policy Research Institute (IFPRI) in collaboration with the Federal Ministry of Agriculture and Water Resources (FMAWR) and funded by the Canadian International Development Agency. APSF was launched in August 2007, and on September 20, 2007 a workshop was organized that brought together stakeholders to discuss the emerging issues in agriculture policy and the implementation of the APSF. The objectives of this stakeholders workshop were: to discuss the emerging issues for agricultural policy in Nigeria and how APSF can support these issues; to share information on the APSF Program and its initial activities; to receive feedback on these initial activities; and to initiate discussions on year-2 activities. This workshop was held at the Chelsea Hotel in Abuja, Nigeria on September 20 2007. There were more than 70 participants from FMAWR, other ministries and agencies, farmer organizations, development partners, academia, and the private sector (see appendices A and B for the agenda and participants list). The workshop opened with remarks from Ms. Pepple, Permanent Secretary, FMAWR; Ms. Julia Bracken, Head of Cooperation, Canadian International Development Agency (CIDA); and Dr. Shenggen Fan, Division Director, IFPRI. This report provides a brief review of the presentations delivered during the workshop, key comments from the audience, and the next steps.